Impact of Quantisal® Oral Fluid Collection Device on Drug Stability - Riggio, Michela; Dave, Keyur A.; Koscak, Branko; Blakey, Mark; Appleton, Charles (Frontiers in Toxicology, 2021)
The stability of drugs can affect drug tests and interpretations. A comprehensive study to verify drug stability in Quantisal® oral fluid (OF) collection device was undertaken in accordance with Australian standard, AS/NZS 4760:2019 (SAI-Global, 2019). The evaluation was performed for the following drugs: (±) amphetamine, (±) methylamphetamine, (±) 3,4-methylenedioxymethylamphetamine (MDMA), (−)Δ9-tetrahydrocannabinol (THC), cocaine, benzoylecgonine, morphine, codeine, and oxycodone. Stability was assessed at four different storage temperatures over seven time points at ±50% cut-off concentrations (Appendix A, Para A4-4.1, AS/NZS 4760:2019) (SAI-Global, 2019). All drugs were found to be significantly more stable at 4 and –20°C, with stability spanning at least 14 days with percentage change within ±20% from the cut-off concentrations (SAI-Global, 2019). In addition, we report a variation trend with cocaine and benzoylecgonine at elevated temperatures, suggesting hydrolytic decomposition of cocaine and a concomitant increase in benzoylecgonine quantitative values. We confirm the cross-talk by showing that the percentage change in the profile of average cocaine-benzoylecgonine measurement is within the acceptance concentration range of ±20%. This finding highlights the importance of precaution during storage and careful considerations during subsequent interpretation of liquid chromatography-mass spectrometry (LCMS) measurements.